Screening Surface‐Defective Graphene Quantum Dots: Promoting Plant Growth and Combating Phytovirus - Guo, Shengxin; Xu, Ying; Wang, Ya; Guo, Renjiang; Tang, Yao; Chen, Moxian; Lv, Menglan; Wu, Jian (Small (Weinheim an der Bergstrasse, Germany), 2025)
Reduced graphene quantum dots (r‐GQD), graphene oxide quantum dots (GOQD), and carboxylated graphene quantum dots (C‐GQD) are screened to promote tobacco growth and combat tobacco mosaic virus (TMV). First, a 21‐day foliar exposure is employed to explore GQDs’ impacts on N. benthamiana. Surface‐defective GOQD and C‐GQD are screened out to facilitate N. benthamiana uptake through leaf stomata, and to promote seedlings of differently leaf ages to various degrees at different concentrations after different durations of foliar exposure. Specially, compared to the ddH2O treatment, GOQD/C‐GQD at 400 mg L−1 increase biomass by 44%/68%, increase chlorophyll content by 43%/54% and up‐regulate the expression of growth‐related genes NtLRX1, CycB, and NtPIP1 by more than two‐fold. Second, different from the transient inhibition shown by r‐GQD and the TMV enhancement shown by GOQD, C‐GQD can directly inactivate TMV infection by inducing TMV aggregation and attachment outside TMV, significantly decreasing TMV replication and hindering TMV spread over 21‐day. Specially, C‐GQD decreases the transcript abundance of TMV RdRp and TMV CP to 0.11‐fold and 0.29‐fold, and down‐regulates the host defensive response pathways. This work provides a comparative analysis of GQDs with different surface‐functionalizations, highlighting C‐GQD as a promising nanotechnology tool for promoting plant growth and inactivating phytovirus. A comparative analysis of three GQDs in promoting tobacco growth and combating tobacco mosaic virus is provided. C‐GQD is screened out to serve as a plant‐friendly agent that directly inactivates TMV rather than inducing plant immunity. The sustainable application of C‐GQD in agriculture offers novel directions and new insights not only in promoting plant growth but also for controlling phytovirus.